Underuse of recommended treatments among people living with treatment-resistant psychosis - Lappin, Julia M.; Davies, Kimberley; O'Donnell, Maryanne; Walpola, Ishan C. (Frontiers in Psychiatry, 2022)
Background International guidelines recommend that individuals with treatment-resistant psychosis must be treated with clozapine. ECT has also been reported to improve symptom profiles. Identification of clozapine and/or ECT use in real-world practice enables understanding of the extent to which this evidence-base is implemented. Setting Statewide public health tertiary referral service, the Tertiary Referral Service for Psychosis (TRSP), NSW, Australia. Objectives To (i) describe clinical characteristics of individuals with treatment-resistant psychosis and to detail the proportion who had received a trial of clozapine or ECT at any point during their illness course; (ii) describe the characteristics of the treatment trials in both those currently on clozapine and those previously on clozapine; (iii) document reasons in relevant individuals why clozapine had never been used. Methods All TRSP clients who met the criteria for treatment resistance (TR) were included. A detailed casenote review was conducted to examine whether clozapine and/or ECT had ever been prescribed. Characteristics of clozapine and ECT trials were documented. Tertiary service treatment recommendations are described. Findings Thirty-six of 48 individuals had TR. They had marked clinical and functional impairment. A minority were currently receiving clozapine (n = 14/36). Most had received a clozapine trial at some point (n = 32/36). Most experienced persistent clinical symptoms while on clozapine (n = 29/32). Clozapine plasma levels were very rarely reported (4/32). Augmentation and antipsychotic polypharmacy were common among those currently on clozapine. The median clozapine trial duration was 4.0 (IQR: 3.0–20.3) months in individuals previously prescribed clozapine. Reasons for clozapine discontinuation included intolerable side effects (n = 10/18) and poor adherence (n = 7/18). One-quarter of TR individuals had trialed ECT (n = 9/36). Tertiary service recommendations included routine plasma monitoring to optimize dose among people currently on clozapine; clozapine retrial in those previously treated; and clozapine initiation for those who had never received clozapine. ECT was recommended to augment clozapine and as an alternative where clozapine trial/retrial was not feasible. Conclusion Among people with TR referred to a tertiary service, clozapine and ECT were underutilized. Clozapine trials are typically terminated without an adequate trial. Strategies to optimize the use of clozapine therapy and ECT in clinical settings are needed to increase the therapeutic effectiveness of evidence-based therapies for treatment-resistant psychosis.